Transmissibilidade da vibração e distribuição da pressão na interface assento-operador de tratores agrícolas em condições dinâmicas - Roth, Claudio Weissheimer (2010)
Substantive changes introduced in the agricultural work, driven by further increases in productivity in the agricultural machinery are the basis of this study. The tractor is a machine used in most activities of tillage, by concentrating most of the physical and mechanical actions to perform these activities. The tractor seat is one of the most important factors to be considered in the design of the workplace, it is the area where the operator remains for hours. The aim of this study was to analyze the transmissibility of vibration and pressure distribution in the seat-operator interface in two types of seats in agricultural tractors, in two settings for suspension in three forward speeds and three different types of micro-reliefs. Were performed simultaneous field experiments with measurements of amplitude of vibrations and pressure distribution on a path of 40 meters in three distinct areas, consolidated, ploughed and asphalt, in three average speeds, 4.66, 5.57 and 6.58 km/h. The data of operator exposure to whole body vibration were obtained through the RT Pro Photon 6.30 system, which performs simultaneous readings in the triaxial axes x, y and z and to measure the pressure distribution was used a blanket sensorized interface module of the X-sensor system. Later, the parameters which allowed the evaluation of the transmissibility of vibration were calculated, as well as the distribution of pressures on the trunk of the operator in the seat. Was performed an Analysis of Variance (ANOVA) and Duncan Test. The level of significance was the 95% reliability. It was concluded that in consolidated and ploughed areas the effective accelerations exceeded the upper limit of the little discomfort zone of standard 2631-1:1997 and that the actual magnitude of the transmissibility of vibration increased on frequencies of 2.5 and 12.5 Hz. The maximum limit of comfort and daily work of eight hours have been overcome by the magnitude of the effective accelerations in all the tests and by the accelerations in more than one direction, in the frequency ranges of 2.5 and 5 Hz on consolidated and mined areas. The values of the average pressures of seat B1 were around 25% lower than the seat B2 medium pressure on consolidated and ploughed areas and their distribution was similar between the two benches, regardless of the setting of the suspension regulation. The dynamic capability to mitigate sudden changes of pressure of seat B1 was higher in regulation R1 and on seat B2, in the regulation R2, considering that on the wrought soil regulation R2 of seat B2 showed an ability to reduce the sudden pressure 50% lower than the regulation R1. Areas of effective contact in the seat-operator interface were 20% higher on the seat B1 than seat B2.